Angiotensin I-converting enzyme inhibitory and antioxidative activities of the bioactive peptides in the crude salt-soluble protein hydrolysates of pili nut (Canarium ovatum Engl.) cv. mayon kernel - Gamba, Ella Mae; Uy, Lawrence Yves C.; Torio, Mary Ann O. (2023)
The in silico enzyme digestion and peptide function annotation of pili nut (Canarium ovatum Engl.) 11S globulin protein sequence revealed the presence of bioactive peptides with antihypertensive and antioxidative activities. Molecular docking simulations showed that the proline-histidine (PH) ligand can better inhibit angiotensin I-converting enzyme (ACE) activity than captopril. This result was verified through biochemical assays. Pili kernel protein was extracted with 0.5 M NaCl buffer using the modified Osborne fractionation method, which yielded 100 mg of protein per gram of defatted pili kernel determined via Bradford assay. SDS-PAGE suggested that the protein extract had a major legumin-like (11S) globulin structure with an approximately 57 kDa molecular weight. Enzymatic hydrolysis using pepsin, thermolysin, α-chymotrypsin, and trypsin was used to release the potential antihypertensive and antioxidative peptides with an average rate of 0.03869 mm2 h-1, estimated from band intensity. The hydrolysates were tested for ACE inhibition and free radical scavenging. Captopril and enalapril had %ACE inhibitions of 74.02 and 83.57 %, respectively, whereas the 6 h hydrolysates had a peak %ACE inhibition of 99.73%. These same hydrolysates however, only had 51.32% 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity compared to ascorbic acid, which had 75.59%. These results showed the potential of pili nut as a functional food, especially for preventing high blood pressure and other cardiovascular diseases.
Keywords: Pili nut; Enzymatic analysis; Nuts -- Therapeutic use